Application of the failure mode, effects and criticality analysis in prison to improve safety and mental health - Gioiello, Giovanni; Caiazzo, Andrea; Quagli, Federico; Arnone , Anna; Curcio, Felice; Aviles Gonzaléz, César Ivan; Notarnicola, Ippolito (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Admission to a correctional facility represents a critical phase requiring immediate healthcare attention, with a specific focus on mental health. Inmates show a significantly higher prevalence of psychiatric disorders compared to the general population, and the prison environment may worsen pre-existing conditions or contribute to the onset of new psychological issues. Italian regulations require a clinical assessment at intake, including screening for suicide risk. However, early identification of mental disorders and access to adequate care remain critical challenges. Materials and Methods: This study analyzed the healthcare intake process in an Italian correctional facility using the Failure Mode, Effects, and Criticality Analysis (FMECA). A multidisciplinary working group divided the process into seven operational phases, identifying 34 Failure Modes (FM). Each FM was assigned a Risk Priority Index (RPI) to identify critical areas and define possible improvement strategies. Results: The most critical phases were "Request for tests and specialist consultations" and "Collection of medical and personal history”. Major contributing factors included organizational inefficiencies, language barriers, delays in psychiatric evaluations, and failure to report psychological symptoms. Conclusions: Three key corrective actions were identified: implementing standardized checklists, multilingual medical documentation, and staff training in managing psychological distress.